Digital Marketing and Consumer Experience in Building Brand Equity to Improve Consumer Repurchase Intention in Cold ’N Brew - Dimas Adi Nugroho; Ihwan Susila; Rini Kuswati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This examine aims to analyze the influence of digital marketing and consumer experience in building brand equity to increase repurchase intention at Cold'n Brew coffee shop. The research approach used is quantitative, with the study population including consumers at Cold'n Brew coffee shop, with a sample size of 211 respondents. The research employs a non-probability sampling approach, specifically utilizing purposive sampling to identify respondents deemed most relevant to the study’s objectives. Data were gathered through a structured questionnaire designed based on the Likert scale to measure participant responses with consistency and reliability. Analytical procedures were executed using Partial Least Squares (PLS) methodology via the SMARTPLS software version 3.2. The evaluation of the structural model was conducted in two distinct phases: assessment of the measurement (outer) model and the structural (inner) model. Empirical findings demonstrate that both digital marketing strategies and consumer experience exert a statistically significant and positive influence on brand equity as well as on consumers’ intention to repurchase. Moreover, brand equity itself has a significant and positive effect on repurchase intention. Notably, brand equity serves a mediating role, significantly bridging the impact of digital marketing and consumer experience on repurchase intention. This research makes a valuable contribution to the academic discourse by deepening the understanding of how digital marketing and consumer experience collectively shape brand equity and drive repurchase behavior. These findings can also be a practical reference for business actors, especially coffee shops, in designing more effective marketing strategies that are oriented towards customer loyalty.